Modeling and Simulation of a Separate Line Calciner Fueled with a Mixture of Coal and Rice Husk - Sunu Herwi Pranolo; Yazid Bindar; Dwiwahju Sasongko; Herri Susanto (ASEAN Journal of Chemical Engineering, 2010)
A model has been made to predict performance of a calciner in a cement plant for the use of rice husk as partial substitution of coal. The calciner was assumed as a plug flow reactor with no-mass and heat transfer limitations. The model was composed of three equations of calcination, coal and rice husk combustions with kinetic parameters obtained from literature. Two of 20 sets of operation data were used as base-lines for simulations, namely: Case-A from operation at a capacity of 532 ton h-1 of kiln feed (KF) with coal as a fuel; and Case-B at 530 ton h-1 with 20% rice husk in a mixed fuel. Two simulations were executed at constant total fuel mass flow-rate (21.94 ton h-1 of Case-A and 27.39 ton h-1 of Case-B) and at constant total energy supplied (0.946 and 1.188 GJ ton-1 KF for Case-A and Case-B respectively). Our simulation showed that a target CaCO3 conversion could be obtained using mixed fuel with maintaining constant total energy supplied instead of constant total fuel mass flow-rate. In Case-A as base-line, the use of mixed fuel with 20% rice husk with maintaining constant supplied energy would give a coal saving of 11.8%. This operation however would require an increase in specific fuel consumption from 0.0412 to 0.0455 ton ton-1 of KF. In Case-B as base-line, the CaCO3 conversion of 95% could be obtained with a mixed fuel with rice husk mass fraction up to 40%.